Critical Reflexivity in Indigenous and Cross‐cultural Psychology: A Decolonial Approach to Curriculum?. Issue 3 (2nd December 2018) - Castell, Emily; Bullen, Jonathan; Garvey, Darren; Jones, Nicola
Highlights: Critical reflexivity is a mechanism for working toward decoloniality in higher education. We analyzed Indigenous and cross‐cultural psychology students' written reflections. Analyses revealed that students negotiate experiences of discomfort and uncertainty in the classroom. Findings support the value of discomfort for prompting transformations among students. We pose a commentary on the tensions inherent to accompanying our students in this uncertain space. Abstract: Critical reflexivity is a mechanism for working toward decoloniality in higher education, with the potential to prompt students' to critique the contexts in which they are embedded, and facilitate transformative learning. We present a critical examination of the tensions surrounding decoloniality and critical reflexivity in an undergraduate unit on Indigenous and cross‐cultural psychology at a large Australian university. We invited students in the unit to participate in a written reflexive exercise at the beginning ( N  = 44) and end of semester ( N  = 23) and analyzed these reflections qualitatively for level (four‐category scheme for coding) and content (causal layered analysis) of reflection. Findings suggest that, while students' primarily demonstrate reflective engagement at levels preordinate to critical reflexivity, they are also engaged in active and nuanced processes of negotiating discomfort and uncertainty in this space. We pose critical commentary on the notion of safety in teaching practice, and consider the role of the academic institution in parametrizing the decolonial stance. This research holds application and transferability to higher education settings, and for the enduring project of engaging a decolonial approach to the curriculum within psychology.